Influence of steel and polypropylene fibers addition on selected properties of fine-grained concrete = Wpływ dodatku włókien stalowych i polipropylenowych na wybrane właściwości betonu drobnoziarnistego - Denisiewicz, Arkadiusz; Socha, Tomasz; Kula, Krzysztof; Pasula, Marcin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents results of laboratory tests of selected mechanical and physical properties of fine-grained fiber concrete. Tests were conducted on samples with a different degree of reinforcement made on the basis of steel and polypropylene fibers. For the designed concrete mixtures and prepared samples, slump class, shrinkage, compressive and bending strength and water tightness were determined.
Keywords: fibers; fine-grained concrete; laboratory test; włókna; beton drobnoziarnisty; badania laboratoryjne